A STUDY ON WRITING RECOUNT TEXT - Dian Kusuma (JEE (Journal of English Education), 2015)
The purpose of this research was to find out students’ skill in writing recount text. Recount text was a text that tells the reader to listener what happened in the past through a sequence events. This research used descriptive qualitative research design.The findings showed that the students’ skill in writing recount text at SMAN 2 Rambah Hilir as follows: 1 student (3,33%) was very good category, 11 students (36,7%) were good category, 16 students (53,3%) were fair category, and 2 students (6,67%) were poor category.